Antiplatelet therapy in elderly patients. (April 2011) - Park, Seung-Jung; Park, Duk-Woo; Oh, Jun-Hyok
With remarkable advances of medical care, the aging population is growing rapidly. Cardiovascular disease remains the leading cause of morbidity and mortality in elderly people and therefore antiplatelet therapy has been a mainstay of cardiovascular medicines for reducing and preventing cardiovascular risk in these populations. The benefits of several antiplatelet drugs in the elderly are well documented. However, there are limited data regarding the optimal use of antiplatelet agents considering the risk:benefit ratio in elderly patients, who are more vulnerable to safety issues owing to different pharmacokinetics and pharmacodynamics as compared with young patients. In this article, we review currently available evidence regarding the efficacy and safety of antiplatelet therapy (i.e., aspirin, old and new P2Y12 inhibitors and glycoprotein IIb/IIIa inhibitors) in the elderly for primary and secondary prevention strategies in cardiovascular care.